2020
DOI: 10.1088/1742-6596/1461/1/012009
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of inverse photonic crystals by ETPTA photopolymerization method and their optical properties

Abstract: Inverse photonic crystal films were prepared by photopolymerization of ethoxylate trimethylolpropane triacrylate (ETPTA) using opal-type templates. Their high quality was proved by investigations of structural and optical properties. The unexpectedly high refractive index, nETPTA ≈ 1.67, of polymerized ETPTA was obtained from a numerical approximation of the spectral positions of the reflectance peak of the films at different incidence angles. Fabricated samples were tested as sensors for water-ethanol mixture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The SUS mesh (shown in Figure S10) was introduced to the cathode paste as a conductive fibrous skeleton. The characteristic peak corresponding to acrylic C=C bond 27 of ETPTA was not observed in the FT‐IR spectrum of the fs‐cathode, confirming the successful UV curing of the ETPTA in the fs‐cathode (Figure S11). In addition, the SUS mesh in the fs‐cathode was compactly filled with the cathode components (i.e., NCM811 powders, carbon black, and gel electrolyte) (Figure 2B and Figure S12).…”
Section: Resultsmentioning
confidence: 76%
“…The SUS mesh (shown in Figure S10) was introduced to the cathode paste as a conductive fibrous skeleton. The characteristic peak corresponding to acrylic C=C bond 27 of ETPTA was not observed in the FT‐IR spectrum of the fs‐cathode, confirming the successful UV curing of the ETPTA in the fs‐cathode (Figure S11). In addition, the SUS mesh in the fs‐cathode was compactly filled with the cathode components (i.e., NCM811 powders, carbon black, and gel electrolyte) (Figure 2B and Figure S12).…”
Section: Resultsmentioning
confidence: 76%
“…Previously, we have shown that this exposure is sufficient to complete the polymerization of ETPTA. [ 50 ] Then both glass plates were removed and SiO 2 microspheres etched in 8 vol. % HF for 1 min (Figure 1f).…”
Section: Resultsmentioning
confidence: 99%
“…The sample inherits its template preserving the quality of the structure, as it was previously reported for inverting of continuous opal films with photocurable resins. [50,54,55] SEM images of inverse micropatterned PhCs are shown in Figure 5c and d. In panel (c), the dark gray areas are ETPTA inverse striped patterns, and the light areas are structureless ETPTA spacings.…”
Section: Inverting Of the Samplesmentioning
confidence: 99%
See 2 more Smart Citations